Effective Exciton Dissociation and Reduced Charge Recombination in Thick‐Film Organic Solar Cells via Incorporation of Insulating Polypropylene. Issue 8 (17th May 2019) - Wang, Tong; Yang, Xiao-Yu; Bi, Peng-Qing; Niu, Meng-Si; Feng, Lin; Liu, Jian-Qiang; Hao, Xiao-Tao
Abstract : In organic solar cells (OSCs), the sensitivity of device performance to active layer thickness is a limiting factor for the large‐scale manufacture and roll‐to‐roll production. To reduce the thickness‐dependent effects, a low‐cost insulating polypropylene (PP) material is incorporated into the system with a high crystallinity donor, poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)‐benzo[1, 2‐ b :4, 5‐ b ′]dithiophene))‐alt‐(5, 5‐(1′, 3′‐di‐2‐thienyl‐5′, 7′‐bis(2‐ethylhexyl)benzo[1′, 2′‐ c :4′, 5′‐ c ′]dithiophene‐4, 8‐dione))]:[6, 6]‐phenyl C71 butyric acid methyl ester (PBDB‐T:PC71 BM) and the system with a low crystallinity donor, poly[[4, 8‐bis[(2ethylhexyl)oxy]‐benzo[1, 2‐ b :4, 5‐ b ′]dithiophene‐2, 6‐diyl][3‐fluoro‐2‐[(2‐ethylhexyl)carbonyl]thieno‐[3, 4 b ]thiophenediyl] (PTB7):PC71 BM. The devices based on PBDB‐T:PC71 BM:PP (2 wt%) show a power conversion efficiency (PCE) of 7.6% at a thickness of 280 nm compared with the control device with a PCE of 7% at a thickness of 100 nm. The change is mainly due to the enhancement of the crystallinity of donors with high crystallinity. PTB7:PC71 BM with 4 wt% PP shows higher PCE than the control device for the same thickness (100–300 nm) and reduced PCE with increasing thickness. These are mainly due to the reduced PC71 BM aggregation. The optimization of crystallinity and morphology will further promote effective exciton dissociation, accelerated charge transport, and reduced charge recombination. It indicates that the low cost and simple method of adding PP is a promising option for roll‐to‐roll production in the future. Abstract : The addition of low‐cost polypropylene (PP) into the active layer of organic solar cells improves the crystallinity of donors with high crystallinity and has a slight negative effect on the crystallinity of donors with low crystallinity. PP can reduce the aggregation size of PC71 BM, which leads to optimized morphology of the active layer. These results lead to a high power conversion efficiency at a thick active layer.